Lifecycle Assessments of Railway Bridge Transitions Exposed to Extreme Climate Events - Setsobhonkul, Sadudee; Kaewunruen, Sakdirat; Sussman, Joseph M. (Frontiers in Built Environment, 2017)
Railway track components located at bridge transition zones or approach areas suffer from impact load and vibrations caused by abrupt changes in track stiffness on the bridge and the subgrade. The numerous strategies that can be used to mitigate these abrupt track stiffness changes rely on one of two concepts. The first concept is that of providing a gradual stiffness change, and the second is that of equalizing the track stiffness. A number of such mitigation methods have been developed and implemented over recent decades. Construction activities associated with these methods require various materials, processes, and uses of time, costs, and carbon emissions. In this study, eight of the most common techniques for railway bridge transition mitigation, including under ballast mats, soft baseplates, under sleeper pads, rail pads, embankment treatments, transition slabs, ballast bonding, and wide sleepers are compared. This study benchmarks the costs and carbon emissions of these eight mitigation techniques over the 50 year lifespan of a railway system subject to identical probabilities of four environmental scenarios: a control case, extremely high temperatures, extremely low temperatures, and flash flooding. This unprecedented study systemically investigates the effectiveness of the mitigation methods while considering the effects of 30 and 100 meter bridge span lengths. Our results indicate that railway engineers should adopt different mitigation methods for different scenarios. The soft baseplate is the most appropriate method for a short-span bridge in the control case and the case of flash flooding, while ballast bonding is better for long-span railway bridges. Embankment treatment is recommended for both high and low extreme temperatures. However, its applicability is limited when the differential track stiffness is extremely high. Hence, alternatives that are 5-25% more expensive are proposed in parallel. The alternative methods include ballast bonding, and the under sleeper pad and under ballast mat methods, the latter two of which are designed for different climate scenarios. These recommendations translate novel insights from the systems thinking approach into practice, and will benefit the railway industry significantly over the long term, enhancing both economic and environmental sustainability.